Arrival-time analysis of intravenous digital aortograms in aortic dissection. Issue 2 (February 1988) - Lyons, J; Gershlick, A; Gardener, J; Layton, C
Abstract : Arrival-time analysis was applied to intravenous digital aortograms. A single static image was produced by representing the time to 90% maximum density for each image pixel on a grey scale. Arrival-time analysis confirmed the diagnosis in four of six patients with aortic dissection that had been shown by image subtraction. In a further three patients with no dissection the arrival-time images were normal. In two patients with surgical repair of the ascending aorta, residual false lumens were shown by both subtraction and arrival-time analysis. In one of these cases arrival-time analysis prompted reanalysis of the subtraction image that had previously been interpreted as showing a normal aorta. Arrival-time analysis provides a static image of aortic dissection, which helps to overcome subtraction artefact.